The Welfare Implications of COVID-19 for Fragile and Conflict-Affected Areas - Tabakis, Chrysostomos; Ten, Gi Khan; Merfeld, Joshua D.; Newhouse, David; Pape, Utz; Weber, Michael (World Bank, Washington, DC, 2022)
Understanding the impacts of the COVID-19 pandemic on households’ welfare in areas at the admin-1 level subject to fragility, conflict, and violence is important to inform programs and policies in this context. Harmonized data from high-frequency phone surveys indicate that, at the onset of the pandemic, a higher fraction of households in areas affected by fragility, conflict, and violence reported income declines and a higher fraction of respondents reported that they had stopped working since the beginning of the crisis. Households in areas affected by fragility, conflict, and violence were far less likely to report receiving government assistance than those in other areas. These findings suggest that the initial effects of the pandemic exacerbated preexisting economic gaps between areas affected by fragility, conflict, and violence and other areas, indicating that an even larger effort will be necessary in areas affected by fragility, conflict, and violence to recover from COVID-19, with implications for funding needs and policy as well as program design.